2014
DOI: 10.1111/aab.12120
|View full text |Cite
|
Sign up to set email alerts
|

Spider mite infestations reduceBacillus thuringiensistoxin concentration in corn leaves and predators avoid spider mites that have fed onBacillus thuringiensiscorn

Abstract: Perceived benefits of insecticidal transgenic crops include reduced usage of broad‐based insecticides, and therefore lower risk to non‐target organisms. Numerous studies have documented low or no direct toxicity of Bacillus thuringiensis (Bt)‐derived toxins against non‐target organisms, but there has been less research on (a) effects of secondary pest infestations on Bt expressing in crops and (b) behavioural responses by predators feeding on host arthropods from Bt crops – both topics are investigated in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…For Cry1F and Cry2Ab, 8 days of exposure reduced concentrations relative to no exposure while for Cry1Ac 4 days of exposure led to reduced concentrations. Thus, there is limited support for the findings of Prager et al (2014) relative to changing Cry protein levels in the face of mite infestations, because the protein concentrations did not appear to be clearly related to mite density. Further investigation of this phenomenon may be warranted.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For Cry1F and Cry2Ab, 8 days of exposure reduced concentrations relative to no exposure while for Cry1Ac 4 days of exposure led to reduced concentrations. Thus, there is limited support for the findings of Prager et al (2014) relative to changing Cry protein levels in the face of mite infestations, because the protein concentrations did not appear to be clearly related to mite density. Further investigation of this phenomenon may be warranted.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study found that concentrations of Cry1Ab and Cry3Bb1 proteins in maize leaves were significantly reduced after infestation with T. urticae (Prager et al 2014). However, they did not delineate T. urticae densities on the Bt maize and did not examine the effect of exposure time nor quantify Cry protein concentrations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, possible non-target effects on natural enemies also must be assessed for new types of Bt maize 26 . Such an assessment includes numerous factors, such as expression rates of the Cry protein in different plant tissues over the growing season, ingestability and susceptibility of natural enemies to the Cry proteins 12 , transfer probabilities of Cry proteins to higher trophic levels 17 , feeding ecology of both herbivores and natural enemies 27 , and influence of Cry proteins on predator behavior 28 .…”
mentioning
confidence: 99%
“…In a recent study, Prager, Martini, Guvvala, Nansen, and Lundgren (2014), examined the choice feeding behavior of predatory mites and demonstrated that spider mites cultivated on maize plants expressing Bt toxins (Bacillus thuringiensis) were significantly less preferred compared to spider mites cultivated on maize without the Bt toxins. The study by Prager et al (2014) highlights that predatory mites are able to assess the quality of their prey and underscores the importance of more research into the tri-trophic interactions between the nutritional composition of host plants, feeding and development of herbivorous pests, and the performance of natural enemies.…”
Section: Predatory Insect Preferences Predatory Mites Such Asmentioning
confidence: 99%